A novel energy conservation method for office building lighting system. (26th August 2021) - Xu, Xinyin; Wu, Zhengtian; Fu, Baochuan
There is a trade-off between human visual performance and energy cost. With an open office as the research object, personalised control with demand and daylight adaptation is considered in a lighting system with multiple illumination devices. Each luminaire and workspace is equipped with illumination sensors and intelligent units. The intelligent dimming model of the lighting system is established, and the optimal dimming value of the luminaire is determined by the constraint control algorithm. The summation of the power consumed by all LED lights and the other devices is used as the objective function. Simulation study was conducted in this research work with DIALux to verify the lighting system and control method and the simulation results show that the proposed control strategy can automatically adjust illumination in real time according to the change of daylight and personal demand.